Tinjauan Kritis terhadap Strategi Meningkatkan Partisipasi Politik dalam Pemilihan Kepala Daerah di Bali - Antari, Ni Putu Bayu Widhi; Darma, I Made Wirya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research aims to analyze strategies that can be implemented to increase political participation in regional head elections in Bali. In addition, this research was conducted to identify the strengths and weaknesses of each strategy to increase political participation in regional head elections (pilkada/pemilukada) in Bali. Research methods: This research uses a qualitative approach because the aim of this research is not to measure, but to elaborate effective and efficient strategies in increasing political participation in regional head general elections. This research collects secondary data by collecting journal articles that discuss steps to increase political participation in regional head elections. Results and discussion: Community political participation can be increased in the regional head elections in Bali through five strategies, namely implementing dialogical methods through face-to-face forums, using conventional and/or digital media as political communication media, forming democratic volunteers, and providing friendly facilities disadvantaged group. Each of these strategies has advantages and disadvantages. Implication: By implementing this combination of strategies, community participation in the Bali regional head elections can be maximized so as to increase the legitimacy of the elected leaders.